On Fuzzy Internal Direct Product - Nama, N. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The main aim of this paper is to introduce the concept of a Fuzzy Internal Direct Product of fuzzy subgroups of group . We study some properties and prove some theorems about this concept ,which is very important and interesting of fuzzy groups and very useful in applications of fuzzy mathematics in general and especially in fuzzy groups.